On the legitimacy of international tax law. - Peters, C. A. T. (Doctoral series ;, 2014)
The legitimacy of international tax law has been taken for granted for a long time. The approval of double tax treaties in national parliaments would guarantee the democratic foundation of this field of law. However, changes in society have significantly affected international tax law. Allocation rules to avoid juridical double taxation are complemented with increasingly substantive norms that have a significant impact on national taxing systems. Is the democratic legitimacy of modern international tax law as self-evident as assumed? Current international discussions, e.g. on base erosion and profit shifting (BEPS), clearly illustrate that this is a topic that requires attention. This book demonstrates that there is a strong need to reconsider the structures for democratic international tax governance in the 21st century. The purpose of this study is not only to assess the legitimacy of contemporary international tax law, but also to find ways to improve it. The book focuses on two constitutive elements of this legitimacy: the democratic underpinnings of the legal framework of international tax law and the contribution of social-scientific knowledge to the legitimacy of international tax law. Furthermore, it puts forward some recommendations to safeguard the legitimacy of international tax law for the long term. The first part of the book comprises a study of the sociology of international tax law in the period following the Second World War, including an analysis of the role of international tax neutrality for the development of this field of law. Specific attention is paid to recent developments relating to the exchange of information and the taxation of multinational corporations. The second part constructs a theoretical framework to assess and improve the legitimacy of international tax law, which is mostly based on a thorough analysis of the work of Jürgen Habermas. His views on law and democracy - including the role of civil society and the media - provide a useful perspective to value the legitimacy of international tax law. The third part contains recommendations for the future.